Grid-Connected Inverter Output Impedance Reshaping for Passivity Enhancement and Disturbance Rejection - Zhiwei Bian (IEEE, 2021)
To improve both the stability and the disturbance suppression ability of single-phase grid-connected inverters through LCL filters, this paper proposes an inverter output impedance enhancing control mechanism. The impedance enhancing control mechanism employs a virtual impedance control and a node-voltage feedforward control to ensure sufficient passivity and high amplitude of inverter output impedance over wide frequency range of interest. The proposed control mechanism is realized through combination control of a low-voltage bidirectional voltage-source-converter (B-VSC) connected at the filter capacitor branch and the main inverter. The B-VSC sustains an extra low power without sacrificing the efficiency of the inverter. Both the simulation and experimental results are finally given to verify the validity of the proposed method, which shows the performance improvement of the proposed radial-line inverter system working under variable grid conditions.